Curriculum to Prepare AEC Students for BIM-Enabled Globally Distributed Projects. Issue 4 (1st October 2020) - Anderson, Anne; Dossick, Carrie Sturts; Osburn, Laura
ABSTRACT: Globalization and the increasing adoption of BIM and other technologies in the AEC industry have changed the way we prepare graduates for the digital workplace. This paper presents curriculum design where students from five universities worked together to develop design and construction proposals. This paper describes a collaborative project executed in two parts. Part I included the University of Washington in the USA and IIT-Madras in India. Part II included Washington State University in the USA, and National Taiwan University and National Cheng Kung University in Taiwan. Students from these global universities worked on a multi-disciplinary, interdependent project where teams created 3D models and 4D construction simulations. This curriculum addresses ACCE and ABET accreditation requirements regarding multi-disciplinary teams, ethical and professional responsibilities in global, economic, environmental, and societal contexts, and effective teamwork. In this paper, we describe the course design, evaluative criteria, and lessons learned. We found that it was important to emphasize BIM Execution Planning for distributed teams given that communication and coordination can be challenging across time zones and cultural differences. Working through technical challenges of exchanging BIM data, the students learned coordination skills in a globally distributed team environment that simulated real work experiences.